Emergence of Digital Matrimony: Exploring Islamic Legal Responses to Metaverse Marriages - Fikri, Mursyid; Abbas; Muchtar, M. Ilham; Darlius; Al-Amin, Dzulkifli (Journal of Islamic Thought and Civilization, 2024)
This research examines the Islamic legal perspective on conducting marriages within the virtual realm of the metaverse, by addressing the implications of digital advancements in religious practices and legal frameworks. The study explores how Islamic legal principles can be applied or adapted to virtual marriages in contemporary contexts. Thus, a qualitative methodology is employed that utilises document analysis and in-depth interviews with scholars and experts in contemporary Islamic jurisprudence and technology. This research focuses on assessing the validity, conditions, and execution of virtual marriages, identifying the challenges and potential solutions in aligning these practices with Sharia principles. The results indicate that integrating marriage practices into the metaverse is feasible with appropriate adjustments to ensure compliance with Islamic law, particularly regarding legal, technical, and ethical considerations. The uniqueness of this study stems from its exploration of previously unexplored areas, where digital innovation intersects with religious law, offering new perspectives on the adaptability of Islamic legal principles in response to emerging technologies. The implications of the findings are significant for policymakers, legal practitioners, and Muslim communities, as they provide a strategic framework for developing relevant Islamic legal policies and guidance for virtual interactions, ensuring that the evolving digital landscape respects and upholds religious values.